2020
DOI: 10.1590/0103-11042020e412
|View full text |Cite
|
Sign up to set email alerts
|

Morbimortalidade pela Covid-19 segundo raça/cor/etnia: a experiência do Brasil e dos Estados Unidos

Abstract: RESUMO Este estudo objetivou descrever a experiência do Brasil e dos Estados Unidos da América (EUA) em relação aos dados de morbimortalidade por Covid-19, segundo a raça/cor/etnia. Para isso, procurou-se descrever os fatores envolvidos no tratamento e divulgação dos dados de morbimortalidade por essa patologia nos dois países. Foram analisados boletins epidemiológicos divulgados pelo Ministério da Saúde, resultados parciais da Pesquisa Nacional por Amostra de Domicílio (PNAD) Covid-19 realizada pelo Instituto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 15 publications
0
11
0
10
Order By: Relevance
“…The present results corroborate the findings of Price-Haywood et al 2020 21 and Karmakar et al 2021 22 in which black and brown individuals presented a higher risk of worse prognosis and death by COVID-19. Additionally, Araujo et al 2020 6 reported that hospitalizations amongst black and brown people increased throughout the pandemic in Brazil. The mechanism for higher lethality of black people can be explained by their lower and slower excretion of sodium, which results in the suppression of the Aninnine-Aldosterone-Angiotensin System (AAR), thereby tending towards sodium retention and arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results corroborate the findings of Price-Haywood et al 2020 21 and Karmakar et al 2021 22 in which black and brown individuals presented a higher risk of worse prognosis and death by COVID-19. Additionally, Araujo et al 2020 6 reported that hospitalizations amongst black and brown people increased throughout the pandemic in Brazil. The mechanism for higher lethality of black people can be explained by their lower and slower excretion of sodium, which results in the suppression of the Aninnine-Aldosterone-Angiotensin System (AAR), thereby tending towards sodium retention and arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In Brazil, the death rates due to COVID-19 in brown and black people are three times higher than in white people. 6 This higher susceptibility and the worse outcome could be related to the higher prevalence of diabetes, hypertension, obesity, asthma, and heart disease in brown and black people. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Corroborando com estudos publicados tanto no Brasil como internacionalmente, em relação a raça/cor, os negros apresentaram maior mortalidade no período do estudo [38][39][40] .…”
Section: Discussionunclassified
“…Apesar da insuficiência da inserção do quesito cor, os reduzidos sistemas que permitem a desagregação da variável mostram que a dimensão racial influencia sobremaneira nas situações de saúde, doença e morte da população brasileira e na diferenciação dela no acesso aos serviços de saúde. Ao se analisar o contexto da pandemia de COVID-19, por exemplo, alguns estudos apontam que a ausência de notificação dessa variável, assim como a insuficiência do preenchimento do quesito nos sistemas de informação, têm acarretado subnotificação e subregistro, impedindo a mensuração das iniquidades raciais em saúde na pandemia 26,27 .…”
Section: A Política Nacional De Saúde Integral Da População Negra (Pn...unclassified